(untitled) (Халықаралық қатынастар және халықаралық құқық сериясы, 2020)
The article examines the geopolitical significance of the black sea region for the foreign policy of Russia. The history of Muscovy’s development before the Russian Empire is mainly connected with the process of increasing expansion on the Black sea and in the Caucasus region. Traditionally, the Black sea was considered an internal water for the Russian Empire, and any foreign presence was perceived as a threat. During the Cold war, the black sea region was not of primary importance to NATO and the Soviet Union, primarily due to the weakness of the North Atlantic bloc in the region. The changing balance of power resulting from the collapse of the Organization of Warsaw Treaty and the inclusion of Bulgaria and Romania, and the prospect of Ukraine and Georgia joining NATO, put Russia in a difficult position. The 2008 war against Georgia and the 2014 annexation of the Crimea can be seen as Russia’s attempt to maintain the balance of power in the region. The rapid strengthening of Turkey’s position in the region poses new challenges for Russian policy to ensure its national security in the Black sea and the Caucasus.